Synthesis of N-Benzenesulfonyl-p-Coumaramide from p-Coumaric Acid - Dali, Nasriadi; Dali, Arniah (Al-Kimia, 2018)
N-Benzenesulfonyl-p-Coumaramide has been synthesized from p-qumarid acid. This research aimed to synthesized N-Benzenesulfonyl-p-Coumaramidefrom p-qumarid acid. Targeted coumpound obtained from two steps reaction. Whice were amidation and asilation. Shynthesized product was identified and characterized by melting point, thing Layer Chromatography analysis, FTIR Spectrhophotometer, 1H-NMR, dan 13C-NMR. The result showed the obtained N-Benzenesulfonyl-p-Coumaramide was white solid ( yield 78.58 %) with melting point was 145-147 oC and KLT (SiO2, n-hexane : cloroform = 6 : 4 v/v, Rf = 0.45).